Digital versus conventional implant impressions for edentulous patients: accuracy outcomes. Issue 4 (13th February 2015) - Papaspyridakos, Panos; Gallucci, German O.; Chen, Chun‐Jung; Hanssen, Stijn; Naert, Ignace; Vandenberghe, Bart
Abstract: Purpose: To compare the accuracy of digital and conventional impression techniques for completely edentulous patients and to determine the effect of different variables on the accuracy outcomes. Materials and methods: A stone cast of an edentulous mandible with five implants was fabricated to serve as master cast (control) for both implant‐ and abutment‐level impressions. Digital impressions ( n  = 10) were taken with an intraoral optical scanner (TRIOS, 3shape, Denmark) after connecting polymer scan bodies. For the conventional polyether impressions of the master cast, a splinted and a non‐splinted technique were used for implant‐level and abutment‐level impressions (4 cast groups, n  = 10 each). Master casts and conventional impression casts were digitized with an extraoral high‐resolution scanner (IScan D103i, Imetric, Courgenay, Switzerland) to obtain digital volumes. Standard tessellation language (STL) datasets from the five groups of digital and conventional impressions were superimposed with the STL dataset from the master cast to assess the 3D (global) deviations. To compare the master cast with digital and conventional impressions at the implant level, analysis of variance (ANOVA) and Scheffe's post hoc test was used, while Wilcoxon's rank‐sum test was used for testing the difference between abutment‐level conventional impressions. Results: Significant 3D deviations ( P  <   0.001) were found between Group II (non‐splinted, implant level) and control. No significant differences were found between Groups I (splinted, implant level), III (digital, implant level), IV (splinted, abutment level), and V (non‐splinted, abutment level) compared with the control. Implant angulation up to 15° did not affect the 3D accuracy of implant impressions ( P  >   0.001). Conclusion: Digital implant impressions are as accurate as conventional implant impressions. The splinted, implant‐level impression technique is more accurate than the non‐splinted one for completely edentulous patients, whereas there was no difference in the accuracy at the abutment level. The implant angulation up to 15° did not affect the accuracy of implant impressions.